ANALISIS PENGARUH PENGGUNAAN CHAT GPT TERHADAP KEPERCAYAAN DIRI DAN KEYAKINAN MAHASISWA DALAM MEMECAHKAN MASALAH MATEMATIKA - Nurjannah, Nurjannah; Heriyanti, Anggy; ., Irmayanti; Khatimah, Husnul (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research is to examine the effect of using GPT Chat on students' self-confidence and confidence in solving mathematics problems. This research is quantitative research using multiple regression tests. Before the regression test is carried out, prerequisite tests are first carried out in the form of normality tests and linearity tests. This research was carried out at the Ahmad Dahlan Islamic University where the population was all students of the Tadris Mathematics Study Program. The sample in this study consisted of 20 people who were chosen randomly using a simple random sampling technique. Based on the results of descriptive statistical analysis and hypothesis testing that has been carried out, it can be concluded that the use of Chat GPT has a positive and significant influence on students' self-confidence and confidence in solving mathematical problems. These results are supported by social cognitive theory, which states that interaction with technology such as Chat GPT can increase self-confidence through modeling, positive feedback, and increased self-efficacy. In addition, educational technology theory emphasizes that the use of technology in learning supports a constructivist approach, creates personalized learning experiences, and develops critical skills. Overall, the results of this analysis provide an in-depth understanding of how the use of Chat GPT can increase students' self-confidence and confidence in solving mathematical problems, as well as supporting theoretical implications from the perspective of social cognitive psychology and educational technology.